Correlation Analysis of Academic Perfectionism, Self-Efficacy, and Burnout among English Department Learners - Diba Ramadhana; Yazid Basthomi; Evynurul Laily Zen (Universitas Hamzanwadi, 2023)
Within applied linguistics and foreign language pedagogy, the role of emotions in language learning has been somewhat overshadowed. Addressing this oversight, our study focuses on psychological elements pertinent to English learning stages. We explore the interplay between academic perfectionism, self-efficacy, and language learning burnout. Survey data was collected from 263 English Department students at a university in Malang across the 2nd, 4th, and 6th semesters using structured questionnaires. Notably, while second-semester students showed no significant correlation among these variables, meaningful connections emerged for students in the fourth and sixth semesters. Analysis revealed that, though academic perfectionism plays a role, its impact on burnout is relatively minor compared to self-efficacy. There was a distinct correlation between academic self-efficacy and language learning burnout throughout the English program's progression, with a weaker relationship in the 2nd semester and a stronger one in the 4th and 6th semesters. The results underscore the need for an educational environment that champions growth over mere perfection. Prioritizing stress management, self-reflection, and goal setting is paramount. Furthermore, specialized support is vital to cater to students' shifting needs as they advance academically.